Case report: Timing of eculizumab treatment in catastrophic antiphospholipid syndrome - Carrara, Camillo; Mataj, Blerina; Gastoldi, Sara; Ruggenenti, Piero; Sciascia, Savino; Roccatello, Dario (Frontiers in Immunology, 2024)
Catastrophic antiphospholipid syndrome (CAPS) is a life-threatening condition of small-vessel thrombosis with acute multiple-organ involvement, and visceral damage. We present a case of a patient with CAPS refractory to conventional therapy. For the first time in a patient with CAPS, marked C5b-9 formation was demonstrated on microvascular endothelial cells, suggesting the usefulness of therapeutic complement inhibition in this setting. Eculizumab, a C5-blocking monoclonal antibody, which is remarkably effective in the treatment of different forms of thrombotic microangiopathy by controlling complement system hyperactivation, halted the "thrombotic storm" and promptly achieved full recovery of thrombocytopenia. However, kidney function didn't recover, possibly because eculizumab was administered too late. Conceivably, timing of treatment is crucial to achieve disease remission before irreversible structural damage occurs in target organs preventing their complete functional recovery.